The genetic population structure and diversity of the endangered bittering Pseudorhodeus tanago revealed by SNP markers - Yoshimitsu Takada; Takahiro Morosawa; Masaki Asano; Ryoichi Tabata; Hitoshi Kubota; Katsutoshi Watanabe (Ichthyological Research, 2026)

Eight new resin glycosides, calyhedins XXIV–XXXI, from the rhizomes of Calystegia hederacea - Masateru Ono; Yosuke Matsuoka; Ryota Arakawa; Hiroyuki Shimadzu; Takumi Nagasawa; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Kazumi Yokomizo; Hitoshi Yoshimitsu; Ryota Tsuchihasi; Masafumi Okawa; et al. (Journal of Natural Medicines, 2025)
Eight new resin glycosides, named calyhedins XXIV ( 1 )–XXXI ( 8 ), were isolated from the rhizomes of Calystegia hederacea Wall. (Convolvulaceae), along with six known calyhedins: calyhedins II ( 9 ), III ( 10 ), IV ( 11 ), V ( 12 ), VIII ( 13 ), and XII ( 14 ). Their structures were determined from the spectroscopic data. Compounds 1 – 7 were hexa- or hepta-glycosides with macrolactone structures (jalapins), and their sugar moieties were partially acylated by five organic acids, including 2 S -methylbutyric, ( E )-2-methylbut-2-enoic, and 2 R -methyl-3 R -hydroxybutyric acids. Compounds 1 – 7 were macrolactones with 22- ( 1 , 7 ), 23- ( 2 ), 27- ( 3 – 5 ), or 28- ( 6 ) membered rings. Compound 8 was identified as an acylated glycosidic acid methyl ester, corresponding to the compound in which the lactone ring of 1 was cleaved and subsequently methylated. In addition, the cytotoxic activities of 1 – 8 , 11 , 12 , and 14 against HL-60 human promyelocytic leukemia cells and the antiviral activities of 1 – 14 and 11 previously isolated calyhedins against herpes simplex virus type 1 (HSV-1) were evaluated. Except for 1 , the other ten tested compounds exhibited cytotoxicity against HL-60 cells, with the IC 50 values of 3 , 4 , 6 , 7 , 11 , and 12 being closer to or rather lower than that of the positive control cisplatin. Additionally, all tested compounds demonstrated anti-HSV-1 activity, with seven compounds, i.e., 3 , 6 , 9 , 10 , 22 , 23 , and 24 , having EC 50 values lower than or comparable to that of the positive control acyclovir. Graphical abstract

Four new acylated glycosidic acid methyl esters and a new glycosidic acid from Ipomoea lacunosa seeds - Masateru Ono; Renjyu Murakami; Shin Yasuda; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo (Journal of Natural Medicines, 2025)
Resin glycosides, characteristic of plants of the Convolvulaceae family, are well-known purgative constituents found in traditional medicinal crude drugs, such as Rhizoma Jalapae, Rhizoma Jalapae Braziliensis, Orizaba Jalapa Tuber, and Pharbitidis Semen. The isolated compounds exhibited a wide range of biological activities, including antibacterial, ionophoric, anti-inflammatory, antiviral, and multidrug-resistance-modulating properties, as well as cytotoxicity against cancer cells. Ipomoea lacunosa L. (Convolvulaceae) is an herbaceous vine native to the United States. Four new acylated glycosidic acid methyl esters ( 1 – 4 ) and one new glycosidic acid ( 5 ) were isolated from the methanol extract of the plant seed. The structures of 1 – 5 were elucidated using spectroscopic data in conjunction with our previous studies on the components of the crude resin glycoside fraction from I. lacunosa seeds. Compounds 1 and 2 were identified as heptaglycosides, 3 as an octaglycoside, and 4 as a nonaglycoside, all sharing methyl 3 S ,11 S -dihydroxytetradecanoate as a common aglycone. The saccharide moieties were partially acylated by glycosidic acid, 7 S -hydroxydecanoic acid 7- O - β - d -quinovopyranoside, and organic acids, including ( E )-2-methylbut-2-enoic, 2 S -methylbutyric, and 2 R -methyl-3 R -hydroxybutyric acids. Compound 5 was identified as a triglycoside with a new aglycone, 4,11-dihydroxyhexadecanoic acid, which is the first glycosidic acid with a hydroxyl group at C-4 of the aglycone moiety. Graphical abstract

Ten new resin glycosides, ipoalbins I–X, from Ipomoea alba seeds - Nodoka Misuda; Mizuki Watanabe; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Kazumi Yokomizo; Hitoshi Yoshimitsu; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Masateru Ono (Journal of Natural Medicines, 2025)

Eleven new glycosidic acid methyl esters from the crude resin glycoside fraction of Ipomoea alba seeds - Nodoka Misuda; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Masateru Ono (Journal of Natural Medicines, 2024)

Four new resin glycosides from Ipomoea muricata seeds: muricatins XIV–XVII - Masateru Ono; Daiki Tenmaya; Maki Tarumi; Syouri Satou; Kotone Tsuji; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Jian-Rong Zhou; Kazumi Yokomizo; Hitoshi Yoshimitsu; Ryota Tsuchihashi; et al. (Journal of Natural Medicines, 2024)

Two new resin glycosides, muricatins XII and XIII, from the seeds of Ipomoea muricata - Masateru Ono; Saki Taketomi; Hirotaka Nishikawa; Shin Yasuda; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2024)

Five new resin glycosides, calyhedins XI–XV, from Calystegia hederacea - Masateru Ono; Yuki Yamano; Takaaki Shimohara; Nobuyoshi Yuhara; Nodoka Misuda; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Ryota Tsuchihasi; Masafumi Okawa; Junei Kinjo (Journal of Natural Medicines, 2023)

Four new resin glycosides, calyhedins VII–X, from the rhizomes of Calystegia hederacea - Masateru Ono; Takaaki Shimohara; Nobuyoshi Yuhara; Souta Matsubara; Shin Yasuda; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2023)

Identification and characterization of organic and glycosidic acids in the crude resin glycoside fraction from the leaves and stems of Calystegia japonica - Kazutaka Uemura; Saaya Kimura; Yuuki Saito; Syun Koyama; Hirotaka Nishikawa; Shin Yasuda; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Masateru Ono (Journal of Natural Medicines, 2023)

Glutaminase inhibitory activity of umbelliferone isolated from kabosu ( Citrus sphaerocarpa Hort. ex Tanaka) - Atsumi Shimada; Hiroshi Ueno; Masanori Inagaki; Hitoshi Yoshimitsu (Natural Product Research, 2022)

A new steroidal glycoside from the fruits of Solanum myriacanthum - Masateru Ono; Mizuki Shimode; Shuhei Tsutsumi; Shin Yasuda; Masafumi Okawa; Junei Kinjo; Hiroyuki Miyashita; Tsuyoshi Ikeda; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2022)

Two new glycosidic acids, calyhedic acids E and F, in crude resin glycoside fraction from Calystegia hederacea - Masateru Ono; Nao Saito; Haruna Minamishima; Shin Yasuda; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2022)

Two new triterpenoids from the leaves and stems of Lantana camara - Masateru Ono; Asami Hashimoto; Mayu Miyajima; Aimi Sakata; Chisato Furusawa; Mizuki Shimode; Shuhei Tsutsumi; Shin Yasuda; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2021)

Identification and characterization of organic and glycosidic acids in crude resin glycoside fraction from Calystegia hederacea - Masateru Ono; Yoshino Ichihara; Nao Saito; Minami Yamada; Kana Yuuki; Masami Nawata; Shuhei Tsutsumi; Shin Yasuda; Ryota Tsuchihashi; Masafumi Okawa; Junei Kinjo; Hiroyuki Miyashita; et al. (Journal of Natural Medicines, 2020)

Seven new resin glycosides from the seeds of Quamoclit × multifida - Masateru Ono; Maako Azuchi; Misato Ichio; Yuki Jiyoubi; Shuhei Tsutsumi; Shin Yasuda; Ryota Tsuchihasi; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Journal of Natural Medicines, 2019)

Four new resin glycosides, murasakimasarins I–IV, from the tuber of Ipomoea batatas - Masateru Ono; Sena Teramoto; Saori Naito; Asuka Takahashi; Akito Yoneda; Masato Shinkai; Naoki Taga; Sin Yasuda; Ryota Tsuchihasi; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; et al. (Journal of Natural Medicines, 2018)

A new resin glycoside from Calystegia soldanella and its antiviral activity towards herpes - Masateru Ono; Yukiyo Kanemaru; Shin Yasuda; Masafumi Okawa; Junei Kinjo; Hiroyuki Miyashita; Kazumi Yokomizo; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2017)

Two new triterpenoids from the seeds of blackberry ( Rubus fructicosus ) - Masateru Ono; Shin Yasuda; Kaori Nishi; Kazutaka Yamamoto; Satoshi Fuchizaki; Satomi Higuchi; Haruki Komatsu; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Natural Product Research, 2016)

Two new prenylflavonoids from Epimedii Herba and their inhibitory effects on advanced glycation end-products - Keisuke Nakashima; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Yukio Fujiwara; Ryoji Nagai; Tsuyoshi Ikeda (Journal of Natural Medicines, 2016)

A new triterpenoid glycoside from the leaves and stems of Duranta repens - Chisato Furusawa; Shin Yasuda; Hiroshi Tsuji; Show Ito; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Toshihiro Nohara; Masateru Ono (Natural Product Research, 2016)

Two new glycosidic acids, multifidinic acids F and G, of the ether-insoluble resin glycoside (convolvulin) from the seeds of Quamoclit × multifida - Masateru Ono; Kousuke Akiyama; Makiko Kishida; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Kazumoto Miyahara (Journal of Natural Medicines, 2013)

A new diterpenoid from the leaves of Clerodendron trichotomum - Masateru Ono; Chisato Furusawa; Kana Matsumura; Sayuri Noguchi; Shin Yasuda; Masafumi Okawa; Junei Kinjo; Masashi Eto; Koki Yamaguchi; Hitoshi Yoshimitsu; Toshihiro Nohara (Journal of Natural Medicines, 2013)

Components of convolvulin from Quamoclit × multifida - Masateru Ono; Makiko Kishida; Yoshihiro Ikegami; Yoshinari Takaki; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara; Kazumoto Miyahara (Journal of Natural Medicines, 2011)

Study of constituents of Veronicastrum villosulum - Toshihiro Nohara; Ai Nakano; Mona El-Aasr; Tsuyoshi Ikeda; Hiroyuki Miyashita; Hitoshi Yoshimitsu; Kotaro Murakami (Journal of Natural Medicines, 2010)

Three new aromatic glycosides from the ripe fruit of cherry tomato - Masateru Ono; Yuki Shiono; Takayuki Tanaka; Chikako Masuoka; Shin Yasuda; Tsuyoshi Ikeda; Masafumi Okawa; Junei Kinjo; Hitoshi Yoshimitsu; Toshihiro Nohara (Journal of Natural Medicines, 2010)

A new diterpenoid and a new triterpenoid glucosyl ester from the leaves of Callicarpa japonica Thunb. var. luxurians Rehd. - Masateru Ono; Tomoyo Chikuba; Kenji Mishima; Toru Yamasaki; Tsuyoshi Ikeda; Hitoshi Yoshimitsu; Toshihiro Nohara (Journal of Natural Medicines, 2009)

Chromone and flavonol glycosides from Delphinium hybridum cv. “Belladonna Casablanca” - Hitoshi Yoshimitsu; Makiko Nishida; Fumio Hashimoto; Mika Tanaka; Yusuke Sakata; Masafumi Okawa; Toshihiro Nohara (Journal of Natural Medicines, 2007)

Physiological functions of solanaceous and tomato steroidal glycosides - Toshihiro Nohara; Tsuyoshi Ikeda; Yukio Fujiwara; Sayaka Matsushita; Eishin Noguchi; Hitoshi Yoshimitsu; Masateru Ono (Journal of Natural Medicines, 2006)